Tsunamis from the 29 March and 5 May 2015 Papua New Guinea earthquake doublet (Mw 7.5) and tsunamigenic potential of the New Britain trench. Issue 14 (30th July 2015) - Heidarzadeh, Mohammad; Gusman, Aditya Riadi; Harada, Tomoya; Satake, Kenji
Abstract: We characterized tsunamis from the 29 March and 5 May 2015 Kokopo, Papua New Guinea, Mw 7.5 earthquake doublet. Teleseismic body wave inversions using various rupture velocities ( Vr ) showed similar source‐time functions and waveform agreements, but the spatial distributions of the slips were different. The rupture durations were 45 and 55 s for the March and May events, with their peaks at 25 and at 17 s, respectively. Tsunami simulations favored source models with Vr = 1.75 and 1.50 km/s for the March and May earthquakes. The largest slip on the fault was similar (2.1 and 1.7 m), but the different depths and locations yielded maximum seafloor uplift of 0.4 and 0.2 m. Tsunami simulation from hypothetical great earthquakes ( M 8.4 and 8.5) on the New Britain trench showed that tsunami amplitudes may reach up to 10 m in Rabaul, but most tsunami energy was confined within the Solomon Sea. Key Points: First instrumentally recorded tsunamis in the New Britain trench Slow rupture velocities estimated from seismic and tsunami analyses Different tsunamis in earthquake doublet due to different location and depth